Observation of exchange bias below incommensurate antiferromagnetic (ICAFM) to canted A-type antiferromagnetic (cAAFM) transition in nanocrystalline orthorhombic EuMnO3 - Das, Raja; Poddar, Pankaj (RSC Advances, 2014)
Detailed ac and dc magnetic properties of orthorhombic EuMnO3 were studied using a nanocrystalline powder sample. Orthorhombic EuMnO3 nanoparticles of 45 nm average size were synthesised using a hydrothermal method. Zero field cooled (ZFC) and field cooled (FC) magnetisation shows anomalies at similar to 53, 44 and 24 K attributed to paramagnetic (PM) to an incommensurate antiferromagnetic phase (ICAFM), ICAFM to a canted A-type antiferromagnetic order (cAAFM) and spin reorientation transitions, respectively. No indication of a PM to ICAFM transition was observed in either the real or imaginary part of ac magnetisation. The real part of the ac magnetisation curve showed a peak at similar to 24.7 K and anomalies at similar to 46.8 and 21.8 K were observed in the imaginary part of ac magnetisation. Reduction in the width of the thermal hysteresis between the field cooling and heating magnetisation curve was observed with the nanocrystallites (similar to 1 K) compared with the bulk phase (similar to 3 K) EuMnO3. Isothermal magnetisation showed a large value of the exchange bias (2799 Oe at 3 K) below the ICAFM to cAAFM transition temperature.